Removal and recovery of uranium(VI) by waste digested activated sludge in fed-batch stirred tank reactor. (1st October 2018) - Jain, Rohan; Peräniemi, Sirpa; Jordan, Norbert; Vogel, Manja; Weiss, Stephan; Foerstendorf, Harald; Lakaniemi, Aino-Maija
Abstract: This study demonstrated the removal and recovery of uranium(VI) in a fed-batch stirred tank reactor (STR) using waste digested activated sludge (WDAS). The batch adsorption experiments showed that WDAS can adsorb 200 (±9.0) mg of uranium(VI) per g of WDAS. The maximum adsorption of uranium(VI) was achieved even at an acidic initial pH of 2.7 which increased to a pH of 4.0 in the equilibrium state. Desorption of uranium(VI) from WDAS was successfully demonstrated from the release of more than 95% of uranium(VI) using both acidic (0.5 M HCl) and alkaline (1.0 M Na2 CO3 ) eluents. Due to the fast kinetics of uranium(VI) adsorption onto WDAS, the fed-batch STR was successfully operated at a mixing time of 15 min. Twelve consecutive uranium(VI) adsorption steps with an average adsorption efficiency of 91.5% required only two desorption steps to elute more than 95% of uranium(VI) from WDAS. Uranium(VI) was shown to interact predominantly with the phosphoryl and carboxyl groups of the WDAS, as revealed by in situ infrared spectroscopy and time-resolved laser-induced fluorescence spectroscopy studies. This study provides a proof-of-concept of the use of fed-batch STR process based on WDAS for the removal and recovery of uranium(VI). Graphical abstract: Highlights: WDAS adsorbed 200 (±9.0) mg of U(VI) per g at pHeq . 4.6 Carboxyl and phosphoryl groups of WDAS complex U(VI) in solution. HCl and Na2 CO3 can desorb 95% of adsorbed U(VI) from WDAS. Fed-batch STR concentrated 6.05 times U(VI) after desorption compared to the feed.